Influence of Cognitive Biases on Financial Decision-Making: A Bibliometric Analysis - Ananda Amalia Munaz; Ardhelia Rayshinta Ratudyana; Chindy Luisa Charlita Permata Jaya; Khairunnisa Zahra Nabilah; Ridha Alya Nur Hidayah; Margareth Henrika; Muhammad Ramadhani Kesuma (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
This study maps the intellectual structure and thematic evolution of research on cognitive biases in financial decision-making using a bibliometric approach. Data comprising 156 peer-reviewed articles were extracted from the Scopus database and analyzed using VOSviewer software to examine co-authorship networks, keyword co-occurrence, and citation patterns. Publications in this field experienced exponential growth, with 63.5% of the corpus concentrated in 2023-2026. India has emerged as the leading contributor by volume, reflecting a broader Global South turn in behavioral finance research. Overconfidence and behavioral finance dominate the keyword landscape, while financial literacy has emerged as a prominent moderating theme. Co-authorship networks remain fragmented, indicating opportunities for cross-institutional collaboration. Emerging frontier themes include technology-based debiasing, algorithmic bias, and ESG investment bias. Practitioners and policymakers can leverage the knowledge map produced by this study to identify high-impact research domains, prioritize financial literacy interventions, and design nudge-based decision environments that mitigate systematic biases in financial markets. This study provides the first comprehensive bibliometric map of cognitive bias research in financial decision-making covering 1997-2026, identifying collaboration gaps, dominant paradigms, and frontier themes that prior narrative reviews have not systematically captured.